Keputusan Fiktif Sebagai Dasar Pengajuan Gugatan Sengketa Tata Usaha Negara - I Gede Buonsu; A. A. Sagung Laksmi Dewi; Luh Putu Suryani (Warmadewa Press, 2021)
Based on the definition of a state administrative dispute, it can be seen that a State Administrative Dispute has an object in the form of a State Administrative Court, which has been regulated in Article 1 paragraph (9) of Law Number 51 of 2009. State Administrative Court itself can be divided into two, namely negative and positive fictional KTUN regulated in article 3 of the Administrative Court Law and article 53 of the Government Administration Law. This study aims to analyze the arrangement of fictitious TUN decisions according to positive law in Indonesia and to find out the fictional TUN decisions as objects of state administration disputes. This research uses descriptive normative research methods with legal, conceptual and case approaches. The results showed that the decision of fictitious TUN can be divided into two, namely negative fictitious TUN and positive fictitious TUN in which the two rules indirectly cause conflict because they both regulate fictitious TUN but have different meanings, where based on Article 3 is interpreted as a decision rejection (negative fictitious KTUN) while according to the provisions of Article 53 it is interpreted as a decision to grant (positive fictitious KTUN).